Agglomeration challenges among the municipalities of Győr - Porhajas, Gábor László (Észak-magyarországi Stratégiai Füzetek, 2024)
This paper presents the results of my research in the urban area of Győr. My research is based on semi-structured interviews with decision-makers (mayors, deputy mayors) and professional leaders (e.g. chief architects, notaries) of more than 10 municipalities. The aim of the research was to typify, collect and analyse the challenges that municipalities face due to suburbanisation in a comparative analysis. Another important objective was to identify good practices, in particular to capture the specific challenges of different agglomeration municipalities. In most cases, health, education and transport services are the most affected by growing population demand, while more affluent neighbourhoods are looking for better leisure, cultural and sports facilities. The integrated, vision-driven development of these emerging agglomeration areas is hampered by the funding structures and 'project mentality' of the municipalities studied. The main finding of my research is that medium-sized agglomeration municipalities face the main challenges in the study area, where everyday municipal management also poses significant challenges in everyday life.